Księga autografów zwiedzających Zamek. 1932-1933 - Archiwum Biblioteki Kórnickiej (1924-1952) (1932)
Aleksander Kakowski, kardynał; August Hlond, Prymas Polski, 2.07.1933, k. 50.
1000,00
Keywords: Księga wpisów